Strategy planning for optimization of production facilities in manufacturing companies - Sudiman; Agus Syahabuddin (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
PT. XYZ is a steel manufacturing industry that operates in the field of Engine and Valve spare parts with Investment Casting production. The number of product requests that fluctuates every year causes PT. XYZ needs to design optimization of production facilities to meet demand. However, with the investment value required being quite high, there is a need for analysis related to optimizing production facilities for the long term. This research aims to determine the strategic planning of operations and business planning needed to increase production capacity and to determine the corrective steps taken to increase production capacity. This research uses a long-term planning method, namely strategic planning, where with Strategic Planning you can plan organizational goals in detail regarding determining strategies, policies, and strategic programs needed to ensure that strategies and policies have been implemented. Apart from strategic planning, investment value analysis is carried out using Return of Investment (ROI) to measure the level of profit that the company invests in capital. Strategic planning begins by looking at the strengths and weaknesses of the company's current condition using the SWOT method, then continues with operational and business planning, quality policy and planning, quality costs, as well as monitoring and evaluation. The reengineering points in this research are related to strategic planning on optimizing production capacity and investment. Previously 50% of production capacity was planned to be carried out by vendors, whereas after reengineering the focus was on 90% of production capacity provided by internal